KH domain protein RCF3 is a tissue-biased regulator of the plant miRNA biogenesis cofactor HYL1 - Karlsson, Patricia (2015)
The biogenesis of microRNAs (miRNAs), which regulate mRNA abundance through posttranscriptional silencing, comprises multiple well-orchestrated processing steps. We have identified the Arabidopsis thaliana K homology (KH) domain protein REGULATOR OF CBF GENE EXPRESSION 3 (RCF3) as a cofactor affecting miRNA biogenesis in specific plant tissues. MiRNA and miRNA-target levels were reduced in apex-enriched samples of rcf3 mutants, but not in other tissues. Mechanistically, RCF3 affects miRNA biogenesis through nuclear interactions with the phosphatases C-TERMINAL DOMAIN PHOSPHATASE-LIKE1 and 2 (CPL1 and CPL2). These interactions are essential to regulate the phosphorylation status, and thus the activity, of the double-stranded RNA binding protein and DICER-LIKE1 (DCL1) cofactor HYPONASTIC LEAVES1 (HYL1).